Ultrastructural Variations of Antennae and Labia Are Associated with Feeding Habit Shifts in Stink Bugs (Heteroptera: Pentatomidae) - Xinyu Li (MDPI AG, 2021)
The family Pentatomidae (stink bugs) is one of the largest groups in Heteroptera, containing many important pests and natural enemies. They exhibit highly diversified feeding habits and related structural modifications, but the key morphological characteristics associated with feeding habit radiation remain unclear. In the current study, we address this question by analyzing morphological variations of feeding related organs. We compare the ultrastructures of antennae and mouthparts across the chosen 17 species in Pentatomidae, representing both plant feeders and predators from four subfamilies. A strong association between ultrastructural adaptation and feeding habit transition has been revealed. The long, sharp, and hook-like mandibular teeth and maxillary barbs are exclusively present in predatory Pentatomidae, suggesting their tight association with the shift of feeding habit from phytophagy to predation. Significant differences between phytophagous and predatory species are also found in antennal and labial sensilla types and arrangements, implying their important function in food selection. Our data identify a series of key morphological structures associated with feeding habit variations among stink bugs, which will facilitate future studies on adaptive evolution of feeding habits, utilization, and population control of economic species in Pentatomidae as well as in other heteropteran lineages.